DEFICIENCY OF ADAMTS-13 IN SEPSIS PATIENTS AND ITS CORRELATION WITH MORBIDITY/ MORTALITY - Syed Owais Ali (Army Medical College Rawalpindi, 2021)
Objective: To detect ADAMTS-13 deficiency in sepsis patients and its effect on in-hospital morbidity and mortality in adult patients of sepsis.